Correction: Active versus sham transcranial direct current stimulation (tDCS) as an adjunct to varenicline treatment for smoking cessation: Study protocol for a double-blind single dummy randomized controlled trial. - Laurie Zawertailo; Helena Zhang; Noreen Rahmani; Tarek K Rajji; Peter Selby (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0277408.].